Dilute manganese-doped ZnO nanowires for high photoelectrical performance. Issue 94 (23rd September 2016) - Chen, Wei-Hao; Su, Chih-Chuan; Hsieh, Hui-Huang; Chang, Meng-Fan; Ho, Mon-Shu
Abstract : This study developed dilute manganese-doped ZnO (D-(Zn, Mn)O) nanowires using a low temperature hydrothermal method. Abstract : This study developed dilute manganese-doped ZnO (D-(Zn, Mn)O) nanowires using a low temperature hydrothermal method. The material properties of the resulting nanowires were examined using field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and high-resolution transmission electron microscopy (HRTEM). We investigated the optoelectronic properties and energy band transformation of ZnO nanowires doped with various concentrations of Mn according to the photoluminescence (PL) spectrum, Raman spectra, X-ray absorption near edge structure (XANES), and absorption spectrum. UV sensors with individual D-(Zn, Mn)O nanowires were then fabricated using a focus ion beam (FIB) system. The resulting sensor demonstrated outstanding photoelectric performance with faster response speed and short recovery time than those of devices using pure ZnO nanowires. The efficacy of the sensors was evaluated according to the light on–off ratio (Δ I = I light / I dark ). We also proposed a possible mechanism for the UV response of the proposed D-(Zn, Mn)O nanowires and investigated the possibility of using numerical simulation to predict the characteristics of D-(Zn, Mn)O nanowires, via a novel application of density function theory.